1988
DOI: 10.1111/j.1365-3083.1988.tb02338.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Lymphoproliferation, Gamma Interferon Production, and Serum Immunoglobulin G Directed against a Purified 32 kDa Mycobacterial Protein Antigen (P32) in Patients with Active Tuberculosis

Abstract: Twenty-one patients treated for active tuberculosis were examined for immune reactivity to purified protein derivative (PPD) and to a purified 32-kDa protein antigen (P32) from Mycobacterium bovis, strain BCG. Lymphoproliferation of peripheral blood leucocytes to PPD and P32 was positive in 95% and 71% of the patients respectively. A positive IFN-gamma response was detected in 62% against PPD and in 48% against P32. Low blastogenesis and IFN-gamma production were observed, especially in patients with poor gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
100
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(111 citation statements)
references
References 19 publications
10
100
0
1
Order By: Relevance
“…The negative correlation between antibody production and cell proliferation has previously been observed in human tuberculosis [14,[16][17][18]. Our data extend these observations in strongly relating the degree of antibody elevation and depression of the proliferative response to disease severity.…”
Section: Discussionsupporting
confidence: 89%
“…The negative correlation between antibody production and cell proliferation has previously been observed in human tuberculosis [14,[16][17][18]. Our data extend these observations in strongly relating the degree of antibody elevation and depression of the proliferative response to disease severity.…”
Section: Discussionsupporting
confidence: 89%
“…34,35 Many attempts have been made to elucidate the natures of the TB antigens involved in stimulating protective IFN-g production. Actually, it was reported that IFN-g production specific for antigens of M. tuberculosis such as Ag85A, 35,36 Ag85B, 35,37 MTB41, 38 and ESAT-6 39 dramatically reduces in patients with active TB but not in HTR, suggesting that these antigens may be candidate protective antigens. 8 In the case of Ag85A, it was also demonstrated that the reduced production of IFN-g in response to Ag85A was significantly restored in PBMCs 35 after anti-TB chemotherapy in patients with active disease, suggesting that Ag85A-specific IFN-g response might be involved in the clinical phenotype and immunopathogenesis of human active pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…Much recent research has been focused on the protective immunity of the proteins of the Ag85 complex. Other studies showed that the Ag85 protein complex also induces readily elicitable cellular immune responses in cultured PBMC of most HR subjects, and in a few patients with clinically active TB [31,32]. In addition, recent studies showed that serum levels of Ag85, as complexes with fibronectin and IgG, to be significantly increased in patients with active TB, independent of skin test status [31,33,34], and these possibly play a role in systemic anergy in active TB patients by binding to and inactivating specialized T-cell fibronectin produced after antigenic stimulation [33].…”
Section: Discussionmentioning
confidence: 99%